RELATIONSHIPS BETWEEN FINANCIAL MARKETS AND INTEREST RATES - Firdavs Kazakov Farhod ugli (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This paper investigates the multi-scale relationship among interest rates, exchange rates, and stock prices using wavelet transform analysis. Specifically, we employ the maximum overlap discrete wavelet transform (MODWT) on interest rates, exchange rates, and stock prices in the US from January 1990 to December 2008. We utilize wavelet variance, wavelet correlation, and cross-correlation definitions to examine the association and lead/lag relationships between these series across various time scales. Our findings indicate that the relationship between interest rates and exchange rates is not significantly different from zero across all scales. Conversely, the relationship between interest rate returns and stock index returns is significantly different from zero only at the highest scales. The analysis sheds light on the dynamic interactions between these financial variables at different frequencies